Systematic review of sodium thiosulfate in treating calciphylaxis in chronic kidney disease patients. Issue 7 (24th July 2018) - Peng, Ting; Zhuo, Ling; Wang, Ying; Jun, Min; Li, Guisen; Wang, Li; Hong, Daqing
Abstract: Aim: Calciphylaxis is a severe complication of advanced chronic kidney disease (CKD). Sodium thiosulphate (STS), an antioxidant and calcium chelating agent, has been used for the treatment of calciphylaxis. However, its efficacy and safety have not been systematically analysed and evaluated. Methods: MEDLINE, EMBASE, and the Cochrane Library database were systematically searched for case report or cases series on use of STS for calciphylaxis published between July 1974 and October 2016. We extracted data on clinical characteristics, laboratory tests result and medication use. The effective treatment was defined as improvement in skin lesion cicatrisation or pain relief without death. Non‐responding effects were defined as stable skin lesions without remission or exacerbation of the disease in patients who remained alive. All‐cause mortality after STS treatment was defined as death due to exacerbations of calciphylaxis or other complications of advanced CKD. We compared the baseline parameters of the patients as well as the efficacy and mortality of the STS therapy between case report and multi‐case reports. Statistical analyses were performed using SPSS 19. Results: A total of 83 papers were screened, 45 of them ( n = 358) met the inclusion criteria, including 36 case reports ( n = 64) and nine multi‐case reports ( n = 294). The mean age of the patients with calciphylaxis was 58 ± 14 years (range 26–91 years). They were female predominant, accounting for 74.1%. Among the patients with calciphylaxis, 96.1% patients were on dialysis with median dialysis vintage of 44.5 months (range 24–84 months). STS was effective in 70.1% of patients, 37.6% patients died. The proportion of patients with sepsis was higher among those who received intravenous STS. There was no significant difference in efficacy between the different STS administration methods ( P = 0.19). Conclusion: Although the study was unable to assess the efficacy of sodium thiosulphate alone in the treatment of calciphylaxis, it still reveals a promising role of STS as an effective therapy for calciphylaxis. Further prospective studies to define the optimal therapy for calciphylaxis are needed. Summary at a Glance: Calciphylaxis (or calcific uraemic arteriolopathy) is an uncommon condition that generally affects patients with chronic kidney disease. Management is challenging and there is a paucity of evidence‐based therapeutic options. This systematic review assesses the evidence (case reports and case series) for the use of sodium thiosulfate in the treatment of calciphylaxis.